Penerapan Mesin MPS Melalui Smart Environment Dalam Mengembangkan Smart Library - Amalia, Nadia; Tine Silvana R; Elnovani Lusiana (Program Studi Ilmu Perpustakaan dan Informasi, Universitas Islam Nusantara, 2023)
The application of the MPS engine in the UIN Sunan Gunung Djati library is a form of the library’s efforts to develop a smart library. in developing a smart library, the UIN Sunan Gunung Djati implemented an MPS engine which was then socialized during the orientation period for student admissions and campus indroductions as well as through user education through social media and the use of banners as a strategy in the formation of a smart environment. In addition, in forming a smart library environment, the new UIN Sunan Gunung Djati fulfills the library building design, system design, and procedure design. Where the three designs have been implemented properly and with plans to update the library building design, system design, and procedure design can be faster in forming a smart environment as a whole